Optimization of operating conditions of rotary drum bioreactor for lignin peroxidise production by solid state - Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Al-Mamun, Abdullah; Qudsieh, Isam Y.; Suardi, M. (2007)
Solid state bioconversion of empty fruit bunches (EFB) for lignin peroxidase (LiP) by Phanerocheate chrysosporium through optimum operating conditions of a rotary drum bioreactor (RDB) was investigated. The study was carried out in the 50L of RDB fabricated locally for 6 days of treatment. The process conditions such as initial pH of 5.5, inoculum of 5% and moisture content of 60% obtained from previous study were applied for this study. The operating conditions i.e. aeration and agitation rate for the rotary drum bioreactor were optimized by using fractional factorial design. A regression model was developed using experimental data with the consideration of linear, quadratic and interactions effects. The maximum production of LiP was 475.8 U/L while the theoretical yield was 439.6 with the optimum aeration and agitation of 30 l/min and 15 rpm respectively using RDB by solid state bioconversion.